O-24 MRI detection of human motor unit fasciculation in Amyotrophic Lateral Sclerosis. Issue 7 (July 2019) - Whittaker, Roger; Porcari, Paola; Braz, Luis; Williams, Timothy; Schofield, Ian; Blamire, Andrew
Abstract : Objective: To develop a clinically applicable non-invasive method for detecting motor unit fasciculation in patients with Amyotrophic Lateral Sclerosis (ALS). Methods: The lower limbs of 6 healthy controls and 4 patients with confirmed ALS were scanned using a novel diffusion weighted MRI protocol sensitive to micrometer-scale movement of skeletal muscle. Motor unit activity was assessed at rest and during electrical motor nerve stimulation time-locked to scanner acquisition. Results: Incremental stimulation revealed a reproducible pattern of overlapping signal voids with dimensions and temporal profiles consistent with the contraction of single motor units. Patients with ALS showed a significantly higher rate of spontaneous motor unit fasciculation at rest (mean 99.1/min, range 25.7–161 in patients vs 7.7/min, range 4.3–9.7 in controls, p  < 0.05) and a significantly higher percentage muscle cross sectional area in which fasciculation was detected (15.9%, SD 2.8 vs 2.9%, SD 1.6, p  < 0.05). Conclusions: This study is the first use of imaging to detect fasciculation in ALS patients. The technique is quick to perform and entirely pain-free. The ability to detect changes in motor unit function which precede motor unit degeneration may allow earlier diagnosis and recruitment to clinical trials.